PERAN KEPEMIMPINAN KHARISMATIK MEMODERASI MOTIVASI KERJA DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DI DABIN V KECAMATAN TEGAL TIMUR KOTA TEGAL - Pujadi, 1352020104; Sunarto, sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the role of the Charismatic Leadership Moderating Effect of Work Motivation and Professional Competence against Teacherâs Performance in Dabin V Kecamatan Tegal Timur Kota Tegal. The purpose of this study is to examine how the role of the Charismatic Leadership Motivation Moderating Effect of Work Motivation and Professional Competence against Teacherâs Performance in Dabin V Kecamatan Tegal Timur Kota Tegal. The sample in this study is 103 respondents which is obtained based on population of teachers in Dabin V Kecamatan Tegal Timur Kota Tegal. This research uses the primary data obtained by questionnaire. The data analysis method used in this study is linear regression with moderation test. The result of the study shows that work motivation does not have a positive impact on teacherâs performance. Professional competence has a positive and significant impact on teacherâs performance. Charismatic leadership has a positive and significant impact on teacherâs performance. The influence of moderation between charismatic leadership strengthens the motivation with the teachers performance. Charismatic leadership strengthens the relationship between the professional competence with the teachers performance. Keywords : Work motivation, professional competence, charismatic leadership and teacher performance